2001
DOI: 10.1016/s0006-3495(01)76203-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Properties of D-erythro-N-acyl Sphingomyelins and Their Corresponding Dihydro Species

Abstract: We have prepared acyl chain-defined D-erythro-sphingomyelins and D-erythro-dihydrosphingomyelins and compared their properties in monolayer and bilayer membranes. Surface pressure/molecular area isotherms of D-erythro-N-16:0-sphingomyelin (16:0-SM) and D-erythro-N-16:0-dihydrosphingomyelin (16:0-DHSM) show very similar packing properties, except that the expanded-to-condensed phase transition (crystallization) occurs at a lower surface pressure for 16:0-DHSM. The measured surface potential was generally about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
89
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 39 publications
21
89
0
Order By: Relevance
“…The mean open time decreased from 25 to 11.3 ms (2-fold decrease), whereas the mean closed time increased almost 10-fold from 4.5 to 40.2 ms. We want to emphasize that although the spring model we applied here provides a simple and reasonable explanation for the increased activation of the BK channel in SPM membranes observed in this study, other mechanisms could contribute to the activation of the BK channel in SPM membranes, such as direct hydrogen-bonding interactions between SPM and BK Ca channel proteins. When compared with PCs, which have only hydrogen bond-accepting features (two ester carbonyls) in the interfacial region, SPM has amide and hydroxyl groups that can serve as hydrogen bond donors and acceptors; thus, SPM is capable of forming complex intermolecular hydrogen bonds with membrane proteins (60). Further investigations are under way in our laboratory to explore the potential activation of BK Ca channels in SPM membranes by direct hydrogen-bonding interactions between SPM and BK Ca channel proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The mean open time decreased from 25 to 11.3 ms (2-fold decrease), whereas the mean closed time increased almost 10-fold from 4.5 to 40.2 ms. We want to emphasize that although the spring model we applied here provides a simple and reasonable explanation for the increased activation of the BK channel in SPM membranes observed in this study, other mechanisms could contribute to the activation of the BK channel in SPM membranes, such as direct hydrogen-bonding interactions between SPM and BK Ca channel proteins. When compared with PCs, which have only hydrogen bond-accepting features (two ester carbonyls) in the interfacial region, SPM has amide and hydroxyl groups that can serve as hydrogen bond donors and acceptors; thus, SPM is capable of forming complex intermolecular hydrogen bonds with membrane proteins (60). Further investigations are under way in our laboratory to explore the potential activation of BK Ca channels in SPM membranes by direct hydrogen-bonding interactions between SPM and BK Ca channel proteins.…”
Section: Discussionmentioning
confidence: 99%
“…DHSMs extracted from human lenses and dispersed in water, have a transition temperature T m of 43 • C, 9 • C higher than that for SMs from bovine brain (Borchman et al, 1996a). Studies of N-palmitoyl- DHSM,or DHSM(16:0), showed a T m of 47.7 • C, 6.5 • C higher than that of the corresponding unsaturated species SM(16:0) (Kuikka et al, 2001). In addition, the organogels formed by these PLs when dissolved in chloroform also exhibit different thermotropic properties.…”
Section: Structural Differencesmentioning
confidence: 94%
“…The desorption rate of CHol was shown to be 20% slower in DHSM than in SM monolayers (Kuikka et al, 2001). Based on calorimetric and NMR spectral measurements (Epand, 2003), Epand also concluded that CHol can interact more favorably with bilayers of DHSMs than with those containing SMs, and that the fraction of miscible CHol is higher in bilayers of DHSMs.…”
Section: Sms Versus Dhsms: Interactions With Cholmentioning
confidence: 97%
See 1 more Smart Citation
“…They are involved with cell signaling and endocytosis. Several reviews have focused on the function and the nature of the forces that lead to their formation (118)(119)(120)(121)(122)(123)(124)(125). Rafts have been reported in human lens membranes ( 34 ).…”
Section: Raft Protein-lipid Interactionsmentioning
confidence: 99%